Facile Functionalization of Colloidal Gold Nanorods by the Specific Binding of an Engineered Protein that Is Preferred over CTAB Bilayers. Issue 1 (19th October 2012) - Park, Won Min; Choi, Bong Gill; Huh, Yun Suk; Hong, Won Hi; Lee, Sang Yup; Park, Tae Jung
<x xml:space="preserve">Abstract</x> Biomimetic functionalization: CTAB‐covered gold nanorods were functionalized with an engineered GBP‐SpA protein through its preferential binding on the gold surface, while colloidal stability was maintained through in situ removal of free CTAB. The functionalized GNRs could be used for plasmonic biosensing after conjugation of antibody through biomolecular recognition (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>